2011
DOI: 10.1371/journal.pone.0028239
|View full text |Cite
|
Sign up to set email alerts
|

The Nubian Complex of Dhofar, Oman: An African Middle Stone Age Industry in Southern Arabia

Abstract: Despite the numerous studies proposing early human population expansions from Africa into Arabia during the Late Pleistocene, no archaeological sites have yet been discovered in Arabia that resemble a specific African industry, which would indicate demographic exchange across the Red Sea. Here we report the discovery of a buried site and more than 100 new surface scatters in the Dhofar region of Oman belonging to a regionally-specific African lithic industry - the late Nubian Complex - known previously only fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
166
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 194 publications
(174 citation statements)
references
References 77 publications
6
166
0
2
Order By: Relevance
“…A similar expansion model is suggested by another line of evidence, from the Dhofar region (Oman), where a number of stratified and surface sites clearly attest the use of a Nubian (Type 1 and 2) Levallois technology (Rose et al, 2011;Usik et al, 2013). This technology was formerly known in South Egypt, North Sudan, and more sporadically in Ethiopia (Guichard and Guichard, 1965;Van Peer, 1992).…”
Section: Mis 5 Inter-regional Expansionssupporting
confidence: 56%
See 3 more Smart Citations
“…A similar expansion model is suggested by another line of evidence, from the Dhofar region (Oman), where a number of stratified and surface sites clearly attest the use of a Nubian (Type 1 and 2) Levallois technology (Rose et al, 2011;Usik et al, 2013). This technology was formerly known in South Egypt, North Sudan, and more sporadically in Ethiopia (Guichard and Guichard, 1965;Van Peer, 1992).…”
Section: Mis 5 Inter-regional Expansionssupporting
confidence: 56%
“…Conversely, the picture emerging from the most recent data from Arabia (Armitage et al, 2011;Petraglia et al, , 2012Rose et al, 2011;Usik et al, 2013) favors the scenario of major expansion waves from Africa, and maybe from elsewhere, during the humid phases of MIS 5. This is in line with a number of paleoenvironmental factors combined with site distribution in East Africa during the early Middle Stone Age, which suggest that Homo sapiens spread in and out of East Africa during MIS 5 (Basell, 2008).…”
Section: Mis 3 Regional Contractionsmentioning
confidence: 98%
See 2 more Smart Citations
“…The Nubian technology is a specific variant of the Levallois technology (GoderGoldberger et al 2016, Guichard & Guichard 19651968;Usik et al 2013;Van Peer 1992) found within Middle Paleolithic techno-complexes at surface sites across the western High Desert in Egypt (Chiotti et al 2009;Olszewski et al 2005), the central Negev highlands (Goder-Goldberger et al 2016) and Arabia (Crassard & Hilbert 2013;Hilbert et al 2016;Rose et al 2011;Usik et al 2013). Common to these finds is a technological package composed of the Levallois Nubian technology alongside both Levallois centripetal and bidirectional modes of production.…”
Section: Introductionmentioning
confidence: 99%